DESIGN AND IMPLEMENTATION OF CIRCULAR PATCH ANTENNA ARRAY FOR UPLINK AND DOWNLINK IN THE STARLINK LOW EARTH ORBIT SATELLITE COMMUNICATION SYSTEM - Arifin, Hafidz
LEO (Low Earth Orbit} satellites are systems with antenna components orbiting the Earth at altitudes between 500 and 1200 km. LEO satellites are used because they offer significant benefits in providing communication services. Due to their low orbit altitude, these satellite systems deliver communication services with minimal latency. Currently, Starlink is the company with a large consteJJation of LEO sateJJites. Starlink has launched an extensive constellation of LEO satellites to provide broad internet access world wide.